Group Counseling Cognitive Restructuring to Increase Self-Control Against Drugs Users - Putri, Alda Azzahra; Suryati, Suryati; Fitri, Hartika Utami (Grief and Trauma, 2023)
This study entitled "Effectiveness of group counseling cognitive restructuring techniques to increase self-control in drug abusers in Banyuasin class IIA penitentiary". The background of this research is because there are many inmates or andikpas who are unable to control themselves after they leave the Banyuasin Class IIA prison. Therefore the purpose of this research. The first is the self-control description of drug abusers in Class IIA Banyuasin Penitentiary (LAPAS), the level of self-control in drug users is classified as moderate with a moderate qualification value of 75%. Second, the effectiveness of group counseling with cognitive restructuring techniques in increasing the self-control of drug abusers in class IIA Banyuasin correctional institutions (LAPAS), the effectiveness of group counseling with effective cognitive restructuring techniques for increasing self-control in drug abusers in class IIA Banyuasin correctional institutions with a sample of 319 and a population using purposive sampling method results in a sample of 12 people with one group pretest and posttest technique using Wilcoxon test data analysis.